Time management, procrastination and prioritization: a framework for service based learning module / Teng Zhi Peng and Bidayatul Akmal Mustafa Kamil - Peng, Teng Zhi; Mustafa Kamil, Bidayatul Akmal (2017)
There is a large number of students facing difficulties in their time management and do not have sufficient time to perform well in academic task. This concept paper describes the nature of time management, procrastination and prioritization that might influence students' academic performance in higher education institutions and proposes a conceptual framework for service based learning module towards excellent academic performance. This study identifies the constraints of time management among students and describes the best options for their time management. This paper is based on secondary data from several reading and analysis of previous researches and literatures on student time management, procrastination and prioritization. It is found that time management is highly important to academic performance of students. Time management, procrastination and prioritization are related to the academic performance of students. They are strong indicators, which affect academic performance. This study may plug in new contribution to knowledge that the theoretical implication will contribute to fill in the lack or an insufficiency of previous literatures about time management, procrastination and prioritization towards academic performance at Malaysian higher educational institutions. This practical implication of study would help the higher educational institution to strengthen the teaching and learning process through a better time management strategy.